THE TRANSLATION PROCEDURES APPLIED IN THE ENGLISH SUBTITLE OF THE INDONESIAN MOVIE ENTITLED “THE RAID” - SULISTIYOWATI, FEBRINA ELOK ANGGRAENI PROBO (Jurnal Ilmiah Mahasiswa FIB, 2013)
Translation deals with two languages which have different terms ofstructure and culture. Those differences can create difficulties in finding the bestequivalent of the target language (TL) from the source language (SL). Related tothose difficulties, a translator requires the translation procedures. This study iscarried out to reveal the translation procedures applied by the translator intranslating English subtitle of the Indonesian movie entitled "The Raid".This study was a qualitative one, which was conducted through descriptivemethod. Research design was document analysis since the data was the dialogueand the subtitle of "The Raid" movie. In the analysis, the data were analyzed byusing three steps based on the theory of Miles & Huberman, i.e. data reduction,data display, conclusion drawing and verification.The results of the study revealed that the procedures applied by thetranslator involved: addition and transposition (structural procedure), borrowing,cultural equivalent, descriptive equivalent, synonym, addition, deletion/omissionand modulation (semantic procedure). Among all of the translation proceduresproposed by Suryawinata & Hariyanto, only four procedures were not applied inthis study namely subtraction, componential analysis, official translation, andreduction/expansion. In addition, there was no translation solution found for thesentence "Subhaana Rabbiyal a'laa wa bihamdih", so it was called resignationprocedure, the theory proposed by Hariyanto.From the results of the study, some suggestions may be derived. Thetranslator should give more attention to the diction because the result of thetranslation subtitle can indirectly increase the reputation of Indonesian movie. Thenext researcher can broaden this study by analyzing translation procedures appliedin particular objects from other points of view and theories. Keywords: Translation, Translation Procedure, Subtitle, Movie